2020
DOI: 10.1002/tpg2.20040
|View full text |Cite
|
Sign up to set email alerts
|

A multigenotype maize silk expression atlas reveals how exposure‐related stresses are mitigated following emergence from husk leaves

Abstract: The extraordinarily long stigmatic silks of corn (Zea mays L.) are critical for grain production but the biology of their growth and emergence from husk leaves has remained underexplored. Accordingly, gene expression was assayed for inbreds 'B73' and 'Mo17' across five contiguous silk sections. Half of the maize genes (∼20,000) are expressed in silks, mostly in spatiotemporally dynamic patterns. In particular, emergence triggers strong differential expression of ∼1,500 genes collectively enriched for gene onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…The collected silks were dissected into five contiguous segments, named sections A-E, from base to tip (Figure 1A). These sections reflect the spatio-temporal gradient of the silk, and include the microenvironment transition of the silks, as sections A-C were husk-encased, and sections D and E were emerged into the external environment (McNinch et al, 2020). All aforementioned factors are analyzed with the 2014 data set, and the addition of the 2015 data allowed for the analysis of environmental effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The collected silks were dissected into five contiguous segments, named sections A-E, from base to tip (Figure 1A). These sections reflect the spatio-temporal gradient of the silk, and include the microenvironment transition of the silks, as sections A-C were husk-encased, and sections D and E were emerged into the external environment (McNinch et al, 2020). All aforementioned factors are analyzed with the 2014 data set, and the addition of the 2015 data allowed for the analysis of environmental effects.…”
Section: Resultsmentioning
confidence: 99%
“…husk-encased vs emerged silks) drives the observed change in cuticular lipid composition, as well as the product-precursor relationships within the cuticular hydrocarbon-producing pathway. Indeed, a recent transcriptomic atlas for maize silks has identified microenvironment-based differential gene expression for many genes involved in cuticular lipid biosynthesis, and more broadly for genes involved in responses to biotic and abiotic stresses (McNinch et al, 2020). Interestingly, the increase in cuticular hydrocarbon accumulation that is observed in emerged silks of B73, the B73×Mo17 and Mo17×B73 hybrids and, to a lesser extent, Mo17, may provide protection against drought, as for example, the observed increase in alkane accumulation upon drought stress that occurs in soybean and sesame (Kim et al, 2007a; Kim et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown even with more than 50% of pollen germination, the yield of certain field crops was significantly decreased due to the stress‐induced damage to female reproductive organs, indicating pollen viability alone cannot guarantee successful seed set (Bheemanahalli et al, 2019; Chiluwal et al, 2020; Prasad et al, 2017; Turc & Tardieu, 2018). In maize, silk (female) developmental events have been overlooked because of the complexity involved in phenotyping or due to the acropetal development of silk and the short duration of its life span (McNinch et al, 2020). Despite the challenges of phenotyping, silk development in maize was to be the key factor affecting pollination and yield determination (Borrás et al, 2007; Nielsen, 2020; Santos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen genes are highly expressed in Fg, Ta, and Um samples; these genes are involved in the DNA-binding transcription factor activity and are upregulated in these Fg and Um samples but downregulated in Ta infections ( Supplementary Table S12 ). Several genes implicated in the light reaction of photosynthesis were discovered to be highly expressed during abiotic stress conditions ( McNinch et al., 2020 ). This finding clearly indicates that the presence of fungal pathogen in the Z. mays silk may be a crucial factor controlling the photosynthesis processes, functions of the plant cell surface receptor signaling pathway, and hydrogen peroxide catabolic process.…”
Section: Discussionmentioning
confidence: 99%